Evaluation of ICT opportunities from student's perspective in the state of Nagaland, India - K. D Vizo; M Mall; R Rout; P Parida (Cogent Business & Management, 2020)
In the twenty-first century ICT has become a necessity in all walks of life primarily for performing various tasks remotely in a transparent, efficient, cost-effective manner with speed and accuracy. ICT is instrumental in transforming various sectors like transportation, banking, manufacturing, education, employment, health and other essential sectors. Its integration with education system has brought a revolutionary transformation by instilling the spirit of innovation and providing flexible atmosphere of learning. In this age of digital communication, the opportunities created by ICT in the deliverance of various electronic services to the student community are analysed in this study. Thus, the study has been performed by developing a questionnaire initially on four dimensions of student's requirements, i.e., learning, research, job/employment and social contact where ICT has a significant role in generating opportunities. After performing exploratory factor analysis, learning and research are clubbed in one factor and in total 03 factors for further analysis. In order to validate the developed scale, confirmatory factor analysis has been performed on a separate sample. The findings of the study confirm usage of ICT towards fulfilment of student's needs. The research outcome has suggested to set up consortium of higher education libraries as well as creating a database by skill mapping of students for usage in local and national level employment. The same database even will act as a certification from the government for those students who wish to start entrepreneurship and require funding from financial institutions.
Keywords: L83; M10; M12; M54; 650; ICT opportunity; principal component analysis; confirmatory factor analysis; employment; social contact; learning and research